2018
DOI: 10.1017/wsc.2018.45
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of Herbicide-Resistant Waterhemp (Amaranthus tuberculatus) with Soybean

Abstract: Waterhemp [Amaranthus tuberculatus(Moq.) J. D. Sauer] is a troublesome weed occurring in cropping systems throughout the U.S. Midwest with an ability to rapidly evolve herbicide resistance that could be associated with competitive disadvantages. Little research has investigated the competitiveness of differentA. tuberculatuspopulations under similar environmental conditions. The objectives of this study were to evaluate: (1) the interspecific competitiveness of three herbicide-resistantA. tuberculatuspopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Butts et al . () reported that A. tuberculatus populations resistant to two SOA competing with soyabean in pots exhibited slightly lower growth rates than a population susceptible to the same SOA at early growth stages, but at harvest all populations had accumulated the same biomass. Dioecious species, such as A. tuberculatus , can benefit from their genetic diversity and quickly evolve other life‐history traits that could potentially compensate for any fitness penalties during vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Butts et al . () reported that A. tuberculatus populations resistant to two SOA competing with soyabean in pots exhibited slightly lower growth rates than a population susceptible to the same SOA at early growth stages, but at harvest all populations had accumulated the same biomass. Dioecious species, such as A. tuberculatus , can benefit from their genetic diversity and quickly evolve other life‐history traits that could potentially compensate for any fitness penalties during vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…The fitness cost of herbicide resistance can be defined as a reduction in plant productivity and reproduction in a herbicide‐free environment caused by pleiotropic effects of the herbicide resistance mutation (Gressel, ; Vila‐Auib et al ., ). Examples of a fitness penalty are (i) the reduction in offspring that contribute to the next generation by a particular weed population relative to other weed populations (Primack & Kang, ) and (ii) reductions in competitive ability (Butts et al ., ). The fitness cost may be the result of mutations that impede normal plant function, causing a diversion of resources from growth and development processes to the evolved resistance mechanism, or pleiotropic effects from resistance alleles in absence of the herbicide (Vila‐Auib et al ., ) or changes in genome architecture caused by the resistance evolution process (Darmency et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…in which b is the slope at the inflection point, c is the lower limit of the model (μg cm −2 ), d is the upper limit (μg cm −2 ), x is the downwind distance from the nozzle (m), and e is the inflection point distance (m). A variance ratio (F-test) was conducted to determine whether individual or pooled nozzle-type models best fit the data (P ≤ 0.05) (Butts et al 2018d;Oliveira et al 2018).…”
Section: Mylar Cardsmentioning
confidence: 99%
“…were the prominent broadleaf weeds. Amaranthus retroflexus and other members of the genus have been found to be highly competitive with soybean(Butts et al 2018;Van Acker et al 1993b), which likely influenced the results in 2016. At St-Adolphe in 2017, few broadleaf weed species were observed; nevertheless, low densities of volunteer B. napus were present in the row-spacing experiment.…”
mentioning
confidence: 99%